Assessing the Adoption of Social Media for Broadcasting at Armed Forces Radio Abuja and FRCN Precious FM Lafia, Nasarawa State, Nigeria - Osakpamwan, Igunma Elvis; Hope, Gana; Mathias, Musa; Igyuve, Anthony I. (Lembaga Yasin AlSys, 2026)
This study assessed the adoption of social media for broadcasting at Armed Forces Radio Abuja and FRCN Precious FM Lafia, Nasarawa State, Nigeria. Guided by the Diffusion of Innovations theory, the study employed a survey research design using a questionnaire to elicit data from respondents. Given the study population of 157, census sampling was adopted. The findings showed that social media adoption for broadcasting in the selected stations remains at a moderate level, indicating that Nigeria is still in an evolving stage of adoption. The results further revealed that social networking platforms, particularly Facebook, WhatsApp, and Twitter/X, are the primary social media tools used for broadcasting at Armed Forces Radio Abuja and FRCN Precious FM Lafia, as affirmed by the majority of respondents. Although these platforms have been adopted, their level of utilization remains moderate and below optimal, suggesting that the integration of social media into broadcasting practice is still developing. The study also found that social media adoption has both positive and negative implications for broadcasting, although the positive influence appears to be more dominant. These findings highlight the continuing transition of broadcast media in Nigeria toward digital engagement and underscore the need for stronger institutional commitment to effective social media integration. The study concludes that improved adoption and more strategic use of social media platforms are essential to strengthen administrative functions, expand online presence, and enhance audience engagement in the contemporary digital broadcasting environment.